2021
DOI: 10.3389/fpsyg.2021.647596
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Adolescent Communication and Early Adolescent Depressive Symptoms: The Roles of Gender and Adolescents’ Age

Abstract: Positive parent-adolescent communication has been found to be negatively related to adolescent depressive symptoms; however, few studies have investigated the moderating effects of adolescent gender and age on this relationship, especially during early adolescence in China. The present study investigated the joint moderating effects of adolescent gender and age on the linkage of father-adolescent and mother-adolescent communication with adolescents’ depressive symptoms. A total of 11,455 Chinese junior high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 85 publications
4
24
0
Order By: Relevance
“…", all items were rated on a five-point Likert-type scale ranging from 1 (almost never) to 5 (almost always). The previous study has demonstrated this measurement was valid in Chinese adolescents [19]. Cronbach's α in this study was 0.85.…”
Section: Depressive Symptomssupporting
confidence: 58%
“…", all items were rated on a five-point Likert-type scale ranging from 1 (almost never) to 5 (almost always). The previous study has demonstrated this measurement was valid in Chinese adolescents [19]. Cronbach's α in this study was 0.85.…”
Section: Depressive Symptomssupporting
confidence: 58%
“…In comparison to children and adults, adolescents are more likely to be depressed in face of great challenges and stressors without parental support (Potochnick & Perreira, 2010). However, parents can provide adolescents with essential psychosocial resources, such as support and communication, which can increase adolescents' self-esteem and competence against depressive symptoms (Brage & Meredith, 1994;Hunter et al, 2015;Zhang et al, 2021). In contrast, the parent-adolescent relationship deterioration aggravates this problem.…”
Section: Parent-adolescent Relationship and Adolescent Depressive Symptomsmentioning
confidence: 99%
“…According to Zhang et al, (2021) positive parent-adolescent communication protects children from developing mental health problems. A high parent-adolescent communication strengthens parental connectedness, trust, and family cohesion.…”
Section: Communication With Parentsmentioning
confidence: 99%
“…Therefore, parental rejection or acceptance can negatively or positively affect adolescents' mental health. Parental warmth is an upbeat parenting style that positively affects teenagers' mental health (Zhang et al, 2021). Parental rejection is a negative parenting style that creates negative and persistent adverse mental health among adolescents.…”
Section: Communication With Parentsmentioning
confidence: 99%
See 1 more Smart Citation